2004
DOI: 10.1002/gea.20033
|View full text |Cite
|
Sign up to set email alerts
|

Thermoluminescence screening of non‐diagnostic sherds from stream sediments to obtain a preliminary alluvial chronology: An example from Cyprus

Abstract: In this paper, simple thermoluminescence (TL) dating procedures utilizing non-diagnostic sherds from fluvial deposits are described. This approach may provide preliminary insights into the chronology of fluvial sequences in areas where transported ceramics are common, but alluvial chronologies are not well developed. Our method deviates from conventional TL-dating methods in that simple screening measurements are made from small, heavily abraded sherds, and dose rates are estimated rather than being measured f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Thus, many profiling samples that are out of stratigraphic sequence appear to contain redeposited material from the earlier phases of activity at the site, in which the OSL signal has not been reset. Such records are still useful in the interpretation of the history of the site, even though they have been removed from their original context, in the same manner as a survey or recovery of redeposited potsherds (e.g., Deckers et al, 2005;Burbidge et al, 2014).…”
Section: Direct Datingmentioning
confidence: 99%
“…Thus, many profiling samples that are out of stratigraphic sequence appear to contain redeposited material from the earlier phases of activity at the site, in which the OSL signal has not been reset. Such records are still useful in the interpretation of the history of the site, even though they have been removed from their original context, in the same manner as a survey or recovery of redeposited potsherds (e.g., Deckers et al, 2005;Burbidge et al, 2014).…”
Section: Direct Datingmentioning
confidence: 99%
“…Deckers (2006) and Deckers et al (2005) have investigated several major floodplains that emanate from the western and southwestern Troodos, namely those of the Dhiarizos, Ezousas, and Stavros-tis-Psokas rivers. A range of informative sediment profiles is described, but except for two OSL dates, chronological precision is limited to the use of terminus postquem archaeological dating.…”
Section: A Critical Evaluation Of Previous Studies On Cyprusmentioning
confidence: 99%
“…15 km east of Paphos, Fig. 1) have been intensively studied (Deckers 2002(Deckers , 2003(Deckers , 2005Deckers et al 2005) particularly for the post Roman period. These studies suggested that a braided river system may have been active from ca.…”
Section: Holocene Fluvial History Of Cyprus: a Combination Of Naturalmentioning
confidence: 99%